Autonomic dysfunction after moderate-severe traumatic brain injury: symptom spectrum and clinical testing outcomes. Issue 9 (12th August 2022) - Li, Lucia; Vichayanrat, Ekawat; Giovane, Martina del; Lai, Helen; Iodice, Valeria
Abstract : Background: Survivors of moderate-severe traumatic brain injury (msTBI) frequently experience trouble- some unexplained somatic symptoms, which may be attributable to autonomic dysfunction. Methods: We conducted two cohort studies. Cohort 1 comprises msTBI patients (with controls) prospec- tively recruited from a regional referral TBI outpatient clinic, in whom we assessed subjective burden of autonomic symptoms using the Composite Autonomic Symptom Score (COMPASS31) questionnaire. Cohort 2 comprises msTBI patients who had clinical autonomic function testing, retrospectively identified from referrals to a national referral autonomics unit. Results: Cohort 1 comprises 39 msTBI patients (10F:20M, median age 40 years, range 19-76), with median time since injury 19 months (range 6-299), and 44 controls (22F:22M, median age 45, range 25-71). Patients had significantly higher mean scores than controls in the weighted total COMPASS-31 score (p<0.001), and also gastrointestinal, orthostatic and secretomotor subscores (corrected p<0.05). Total COMPASS31 score inversely correlated with subjective rating of general health (p<0.001, rs=-0.84). Cohort 2 comprises 18 msTBI patients (7F:11M, median age 44 years, range 21-64), with median time between injury and testing 57.5 months (range 2-416). Clinical autonomic function testing revealed a broad spectrum of autonomic dysfunction in 13/18 patients. Discussion: Our results provide evidence for clinically relevant autonomic dysfunction after msTBI, even at the chronic stage. We advocate for routine enquiry about potential autonomic symptoms, and demons- trate the utility of formal autonomic testing in providing diagnoses.